2015
DOI: 10.1095/biolreprod.114.123455
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Cloned Mice from Adult Neurons by Direct Nuclear Transfer1

Abstract: Whereas cloning mammals by direct somatic cell nuclear transfer has been successful using a wide range of donor cell types, neurons from adult brain remain "unclonable" for unknown reasons. Here, using a combination of two epigenetic approaches, we examined whether neurons from adult mice could be cloned. First, we used a specific antibody to discover cell types with reduced amounts of a repressive histone mark-dimethylated histone H3 lysine 9 (H3K9me2)-and identified CA1 pyramidal cells in the hippocampus and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…By generating neonatal and fertile adult mice from genetically labeled MT neurons derived from mice up to 4.5 months old, we demonstrate that despite the difficulty in inducing neurons to re-enter the cell cycle, at least some neurons maintain sufficiently plastic and intact genomes to produce an entire animal. While other studies have reported varying degrees of success (or failure) in efforts to clone from non-embryonic cortical neurons, this study is unique because we conclusively demonstrate the donor cell origin and age, and produce the first clones from adult mice older than 6-8 weeks of age (Kawase et al, 2000; Makino et al, 2005; Mizutani et al, 2015; Osada et al, 2002; Osada et al, 2005; Wakayama et al, 1998; Yamazaki et al, 2001). In addition, because we have deciphered full MT neuronal genome sequences, we show that accumulation of mutations during the development and post-mitotic aging of neurons is compatible with seemingly normal embryonic and postnatal development, which has relevance for the use of adult cells in regenerative medicine.…”
Section: Discussionmentioning
confidence: 66%
“…By generating neonatal and fertile adult mice from genetically labeled MT neurons derived from mice up to 4.5 months old, we demonstrate that despite the difficulty in inducing neurons to re-enter the cell cycle, at least some neurons maintain sufficiently plastic and intact genomes to produce an entire animal. While other studies have reported varying degrees of success (or failure) in efforts to clone from non-embryonic cortical neurons, this study is unique because we conclusively demonstrate the donor cell origin and age, and produce the first clones from adult mice older than 6-8 weeks of age (Kawase et al, 2000; Makino et al, 2005; Mizutani et al, 2015; Osada et al, 2002; Osada et al, 2005; Wakayama et al, 1998; Yamazaki et al, 2001). In addition, because we have deciphered full MT neuronal genome sequences, we show that accumulation of mutations during the development and post-mitotic aging of neurons is compatible with seemingly normal embryonic and postnatal development, which has relevance for the use of adult cells in regenerative medicine.…”
Section: Discussionmentioning
confidence: 66%
“…In the absence of the HDAC inhibitor, a similar decline in re-cloning efficiency was observed (Figure 2d). These and numerous other studies reporting the cloning of animals from adult somatic cells, including from adult neurons [32 ], point to a generally greater ability of nuclear transfer to restore full developmental competence to a somatic nucleus than iPS reprogramming. But a systematic and direct comparison of the complementation potential of ntES cells and iPS cells from adult somatic cells is yet to be performed.…”
Section: Functional Tests Expose Differences In Stem Cell Qualitymentioning
confidence: 84%
“…This enables the researcher to identify the effects of the cell type and genotype on cloning efficiency. Following the first birth of cloned mice by Dr. Wakayama [ 83 ], we cloned 13 cell types for the production of cloned mice [ 50 , 66 ]. The conclusions drawn from our research are as follows.…”
Section: Nuclear Transfermentioning
confidence: 99%